Who Generates Demand for Sustainable Energy Transitions? Geothermal Heating in Reykjavík. : RCC Perspectives: Transformations in Environment and Society 2019, no. 2: Energizing the Spaces of Everyday Life: Learning from the Past for a Sustainable Future: Who Generates Demand for Sustainable Energy Transitions? Geothermal Heating in Reykjavík. - Melsted, Odinn (Rachel Carson Center for Environment and Society, Munich, Germany, 2019)
Odinn Melsted traces Reykjavík’s transition from coal to geothermal energy. Melsted shows that, contrary to being an inevitable outcome in Iceland, the shift to geothermal energy was a carefully crafted strategy that required three key factors: sufficient available resources, suitable infrastructure and technologies, and most crucially perhaps, the creation of a new societal demand. This necessitated a strong partnership between government actors and energy users, who succeeded in rebranding geothermal energy as the most viable and desirable energy source.